Materials Selection for Lightweight Automotive Composite Hand Operated Parking Brake Lever Design with a Weighted Property Index Method - Mansor, Muhd Ridzuan; Sapuan, S.M (UPM Press, 2014)
In a typical modern vehicle where the components may rise up to 15,000 parts, the task to select the appropriate material to best suit a required function or application is not an easy task. It is more complicated when the designers is faced by the challenged of having overwhelming information on various materials available at the market to choose from to match the required component function. Thus, the need for a systematic and quantitative material selection process is very important to aid the task in choosing the optimum material which gives the maximum benefits to the component such as in function, cost and reliability. One of the solutions is through a systematic material selection process called the weighted property index method. In this exercise, the weighted property index method is applied in the design of an automotive component. The aim is to identify a new material for the construction of a lightweight automotive hand operated parking brake lever based on the performance requirements set for the component.